Pendampingan Pelaporan SPT OP pada Dinas Koperasi, Usaha Mikro dan Perdagangan Kabupaten Bangkalan dalam Rangka Meningkatkan Tax Compliance - Priska Erma; Muhammad Asim Asy’ari; Rahmat Zuhdi (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The purpose of the Assistance with filing Personal Income Tax Returns (SPT) for Individuals (OP) conducted by the Diploma Three Accounting Study Program, Faculty of Economics and Business, Trunojoyo University Madura at the Cooperative, Micro Business and Trade Office of Bangkalan Regency together with KPP Pratama Bangkalan is an important effort in improving tax compliance among civil servants in the Bangkalan Regency Government. Through socialization activities, tax education, and technical assistance in filling out and reporting tax returns, civil servants at the Bangkalan Regency Cooperative, Micro Business and Trade Office are assisted in understanding their tax obligations and reporting their tax returns correctly and on time. This assistance is intended to increase tax awareness and minimize reporting errors, thereby contributing to improved tax compliance. Despite challenges such as limited resources and active participation, this program is expected to strengthen the culture of tax compliance among civil servants in Bangkalan Regency.